2021
DOI: 10.1097/pec.0000000000002464
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Distal Forearm Fracture Reduction by Pediatric Emergency Physicians

Abstract: Introduction:Fracture reduction under point-of-care ultrasound (POCUS) guidance facilitates measurement of residual angulation or displacement that may not be apparent on examination. Point-of-care ultrasound is without patient or staff exposure to ionizing radiation and enlists no additional staffing resources or patient transfer. Methods:We conducted a chart review of all children who underwent reduction of a distal forearm fracture in the pediatric emergency department over a 2-year period, from September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Closed reduction in forearm fractures provides satisfactory alignment in most pediatric cases. Recent studies show that EM physicians can perform closed reductions to obtain adequate reductions in forearm fractures without orthopedic surgeon intervention or consultation (10,13,(15)(16)(17). Post-reduction angulations for all children younger than 14 years of age were similar and acceptable fracture alignment between EM physicians and OS groups in this study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Closed reduction in forearm fractures provides satisfactory alignment in most pediatric cases. Recent studies show that EM physicians can perform closed reductions to obtain adequate reductions in forearm fractures without orthopedic surgeon intervention or consultation (10,13,(15)(16)(17). Post-reduction angulations for all children younger than 14 years of age were similar and acceptable fracture alignment between EM physicians and OS groups in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Some recent studies conducted on pediatric forearm fractures showed that closed reduction by EM physicians had agreeable fracture alignment and beneficial decreased length of ED stays (10,12,13,17). As there were no orthopedic specialists present in our ED, on-call consultations were required to bring them to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…A single center retrospective study showed excellent results of closed reduction of pediatric forearm fracture executed by pediatric physician under point of care ultrasound, they found also less hospital length of stay in comparison to patients treated by orthopedist without ultrasound 17 …”
Section: Discussionmentioning
confidence: 97%
“…16 A single center retrospective study showed excellent results of closed reduction of pediatric forearm fracture executed by pediatric physician under point of care ultrasound, they found also less hospital length of stay in comparison to patients treated by orthopedist without ultrasound. 17 Currently, a randomized clinical trial is underway to evaluate whether, in the presence of a greenstick forearm fracture without cortical interruption, the PoCUS technique without radiographic confirmation can lead to clinically comparable results to those obtained by studying patients with traditional radiography. 18 According to Entezari et al 19 ultrasound showed high accuracy in detection of shoulder dislocation and reduction and it is an alternative diagnostic method that may reduce cost, time to treat, radiations and need for repeated attempts to reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies over the last 5 years show the accuracy of POCUS-assisted fracture reduction in the ED. [2][3][4][5] Every ED has an ultrasound machine: many emergency physicians have been using POCUS to assist in fracture assessment and management for more than a decade. By adopting POCUS as the modality of choice in fracture reduction, the additional costs of specialised radiation equipment, its storage, safety and maintenance can be circumvented in what are already cluttered EDs.…”
Section: Emergency Department Point-ofcare Ultrasound In Forearm Frac...mentioning
confidence: 99%